Determining Optimum Temperature for Growth and Survival of Laboratory‐Propagated Juvenile Freshwater Mussels. (25th September 2013) - Carey, Caitlin S.; Jones, Jess W.; Hallerman, Eric M.; Butler, Robert S.
Abstract: The effects of temperature on growth and survival of laboratory‐propagated juvenile freshwater mussels of two federally endangered species, the Cumberlandian combshell Epioblasma brevidens and oyster mussel E. capsaeformis, and one nonlisted species, the wavy‐rayed lampmussel Lampsilis fasciola, were investigated to determine optimum rearing temperatures for these species in small water‐recirculating aquaculture systems. Juveniles 4–5 months old were held in downweller buckets at five temperatures. Growth and survival of juveniles were evaluated at 2‐week intervals for 10 sampling events. At the end of the 20‐week experiment, mean growth at 20, 22, 24, 26, and 28°C was, respectively, 0.75, 2.22, 3.27, 4.23, and 4.08 mm for Cumberlandian combshell; 1.35, 3.73, 3.81, 4.90, and 4.70 mm for oyster mussel; and 2.09, 3.96, 4.99, 5.13, and 4.87 mm for wavy‐rayed lampmussel juveniles. Generally, temperature was positively correlated with growth of juveniles. Final mean maximum growth occurred at 26°C for all three species, although no significant differences in growth were detected between 26°C and 28°C. The relationship between temperature and survival of juveniles was less clear. Final survival was 82.5, 89.0, 91.0, 89.5, and 93.5% for Cumberlandian combshell; 73.0, 83.5, 78.0, 78.0, and 68.1% for oyster mussel; and 75.0, 89.5, 87.0, 86.5, and 89.5% for wavy‐rayed lampmussel juveniles at the five temperature treatments, respectively. Based on the species used in this study, results indicate that 26°C is the optimum temperature to maximize growth of juvenile mussels in downweller bucket systems. The ability to grow endangered juveniles to larger sizes will improve survival in captivity and upon release into the wild and will reduce time spent in hatcheries. As a result, hatcheries can increase their overall production and enhance the likelihood of success of mussel population recovery efforts by federal and state agencies, and other partners.